Determining the momentum transfer in regolith-like targets using the TUM/LRT electro-thermal accelerator. (December 2020) - Chourey, Swapnil; Koschny, Detlef; Rott, Martin; Schmausser, Corinna
Abstract: Asteroids are small solid bodies that formed during the early stages of the solar system, even before the formation of our own planet. Asteroids have been known to strike our planet Earth ever since its formation, causing a great threat to all existing life forms. One of the means to avert a potential collision of an asteroid with Earth is to deflect the asteroid away from its trajectory towards Earth by means of an impacting spacecraft. This idea is already part of mission designs such as AIDA (Asteroid Impact and Deflection Assessment). The study of the surfaces of numerous asteroids through spacecraft, ground-based spectroscopic observations and other techniques has revealed that the surfaces of these small bodies are covered with loose, granular, heterogeneous geological material. This is called 'regolith'. If an impactor were to collide with an asteroid, the physical phenomenon that needs to be understood is the reaction of the regolith to the impact. To understand the deflection of the asteroid, the transfer of momentum from the impactor to the asteroid needs to be characterised. The impact can produce ejecta which would also add momentum to the target. Therefore, there are two components to this momentum gained by target body: (1) direct transfer of momentum from the impactor to the asteroid, (2) momentum caused by ejecta flying in the direction opposite to that of the impactor. The momentum transfer can thus be described by the so-called momentum multiplication factor β, which is the ratio of the momentum gained by the target to the momentum of the impactor at the time of collision. In this work, small-scale impact experiments using polyvinylchloride (PVC) projectiles on regolith-like materials and simulants - sand, glass beads and the Johnson Space Center (JSC)-1A lunar regolith simulant - have been conducted. We used the electro-thermal accelerator of the Technical University of Munich (TUM)/Lehrstuhl für Raumfahrttechnik (LRT) to determine the momentum transfer from the projectiles onto these regolith targets. We derived relationships between the kinetic energy and the crater mass and characterized the ejecta cloud. We confirmed the dependency of β on the impact velocity of the projectile (impactor) - higher momentum transfer occurs at larger impact velocities. We have also seen a trend that β gets larger for a lower cohesion and higher porosity of the target material. Thus, a thorough understanding of the regolith properties of AIDA's target asteroid will be crucial towards understanding and determining the momentum transfer. Graphical abstract: Image 1 Highlights: In the light of asteroid deflection missions, small-scale impact experiments on regolith-like materials have been performed. Momentum transfer factor (β) calculations, data analysis, related plots have been shown. Crater mass, kinetic energy relations and ejecta angles have been studied. Results show high dependency of 'β' on the impact velocity and target properties (mainly cohesion, internal friction and porosity).